Pemanfaatan Chitosan sebagai Pengganti Formalin Terhadap Masa Simpan dan Sifat Organoleptik Mie Basah - Ringga Risdiana; Tuntas Bagyono; Lilik Hendrarini (Poltekkes Kemenkes Yogyakarta, 2012)
Wet noodle is a food product with high water level which can reach 52 %. Eventhough, formaline is a harmful chemical which is prohibited for food, nonetheless it is often used for preserving ingredient in wet noodle production. Chitosan is a by-product of shrimp and crab processing which can be utilized as a substitution of formaline. The study was aimed to understand whether the preserving times and organoleptic natures of wet noodle added by chitosan and formaline were different or not. The study was an experiment one with post-test only with control group design. The doses of formaline and chitosan observed were 12, 20 and 28 ppm. The panelist for organoleptic testing were 10 students of Nutrition Department of Yogyakarta Polytechnic of Health. The data which were analysed by using Kruskal Wallis non parametric test revealed that the preserving times of the noodle made between the two chemical was not different (p=0,0962), as wellas for aroma liking among the panelists (p=0,731). However, the score from panelists for color, texture and taste for the two types of wet noodle were different, i.e. p=0,004, <0,001 and 0,009 respectively. It is advised for producer who usually use formaline to start use chitosan as it is safe for the consumers.